Social Exclusion as a Pedagogical Practice in the Economy of the Capitalist World: The Case of School Dropouts in the Formal Costa Rican Education System Among Youths Betwen 12 and 18 Years of Age (2000-2010) - Herra Castro, Ernesto (2012)
This text analyzes the economical, historical, political, social and pedagogical relations that the educational institution has had with the historical development of the capitalist world-economy, establishing a dialectical reading that understands the exclusion of formal education in Costa Rican youth from 12 to 18 years old between the years 2000 and 2010.